2015
DOI: 10.3892/ol.2015.3353
|View full text |Cite
|
Sign up to set email alerts
|

Zinc finger protein X-linked is overexpressed in colorectal cancer and is associated with poor prognosis

Abstract: Abstract. Zinc finger protein X-linked (ZFX) is a zinc finger transcription factor and plays a significant role in the self-renewal ability of embryonic stem cells and various cancers. However, its expression and function in colorectal cancer (CRC) remain unclear. In the present study, we evaluated the expression of ZFX in CRC using quantitative polymerase chain reaction (qPCR), western blot analysis and immunohistochemistry (IHC), and further explored its potential functions in CRC cell lines using cell count… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
19
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 24 publications
0
19
0
Order By: Relevance
“…Similarly, expression of ZFX is high in advanced invasive breast cancers and knockdown of ZFX reduces the proliferation rate of breast cancer cells (Yang et al 2014). High expression of ZFX promotes tumor growth of colon cancer cells and colorectal cancer patients with high ZFX expression have poorer overall and disease-free survival (Jiang and Liu 2015). Moreover, knockdown of ZFX suppresses proliferation and invasion of colon cancer cell lines (Jiang and Liu 2015).…”
Section: Zfx Binds To Cpg Island Promoter Regionsmentioning
confidence: 99%
See 2 more Smart Citations
“…Similarly, expression of ZFX is high in advanced invasive breast cancers and knockdown of ZFX reduces the proliferation rate of breast cancer cells (Yang et al 2014). High expression of ZFX promotes tumor growth of colon cancer cells and colorectal cancer patients with high ZFX expression have poorer overall and disease-free survival (Jiang and Liu 2015). Moreover, knockdown of ZFX suppresses proliferation and invasion of colon cancer cell lines (Jiang and Liu 2015).…”
Section: Zfx Binds To Cpg Island Promoter Regionsmentioning
confidence: 99%
“…In contrast, ZFX, a zinc finger protein (ZNF) that contains a DNA binding domain, has been implicated in the initiation or progression of many different types of human cancers, including prostate cancer, breast cancer, colorectal cancer, renal cell carcinoma, glioma, gastric cancer, gallbladder adenocarcinoma, non-small cell lung carcinoma, and laryngeal squamous cell carcinoma (Zhou et al 2011;Fang et al 2012;Jiang et al 2012b,c;Nikpour et al 2012;Li et al 2013;Fang et al 2014a,b;Yang et al 2014;Weng et al 2015). In these previous studies, it was shown that high expression of ZFX is linked to tumorigenesis, and knocking down ZFX can suppress cellular proliferation and increase the proportion of apoptotic cells (Fang et al 2014a;Jiang and Liu 2015;Yang et al 2015;Yan et al 2016). In addition, high ZFX expression correlates with poor survival of cancer patients (Jiang and Liu 2015;Li et al 2015;Yang et al 2015;Yan et al 2016).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…There exist a number of publications describing the correlation between the expression of ZNF280B and the growth of various types of cancer (5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22). For example, Gunn et al (22) reported that ZNF280B acts as a tumor suppressor in chronic lymphocytic leukemia.…”
Section: Discussionmentioning
confidence: 99%
“…By interacting with DNA and proteins, ZNF proteins can provide links between these molecule types (4). An increasing number of studies has reported that ZNF proteins serve critical roles in human cancers (5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15). For example, ZNF703 acts as an oncogene in invasive gastric carcinoma, and its expression levels are correlated with gastric carcinoma progression (16).…”
Section: Introductionmentioning
confidence: 99%